Long-term outcome of patients undergoing re-exploration for bleeding following cardiac surgery: a SWEDEHEART study. (29th March 2022) - Heimisdottir, Alexandra A; Nielsen, Susanne J; Karlsson, Martin; Jeppsson, Anders; Gudbjartsson, Tomas
Abstract: OBJECTIVES: Excessive bleeding leading to re-exploration is a severe complication of cardiac surgical procedures, associated with early postoperative morbidity and mortality. Less is known about the long-term outcome of these patients. We evaluated the impact of re-exploration after cardiac surgery on peri- and postoperative morbidity and mortality, as well long-term mortality, in a well-defined nationwide population. METHODS: In this retrospective study, 48 060 consecutive patients undergoing coronary artery bypass grafting (CABG) and/or valve surgery from 2006 to 2015 were analysed. Multivariable logistic regression was used to identify factors associated with re-exploration, morbidity and mortality. Cox regression analysis was implemented to explore the association between re-exploration and long-term mortality. The mean follow-up time was 4.6 years (range 0–10 years) with follow-up time set at 31 December 2015. RESULTS: Overall, 2371 patients (4.9%) underwent re-exploration. Factors associated with re-exploration included advanced age, procedures other than isolated CABG and acute surgery. Re-explored patients had an increased risk of unadjusted mortality at 30, 90 and beyond 90 days (all P < 0.001). Significance was maintained after adjustment at 30 days [odds ratio: 3.94, 95% confidence interval (CI): 3.19–4.85, P < 0.001] and 90 days (odds ratio: 3.79, 95% CI: 3.14–4.55, P < 0.001), but not with long-term mortality (hazard ratio: 1.02, 95% CI: 0.91–1.15, P = 0.712). Furthermore, re-exploration was independently associated with other postoperative complications, e.g. prolonged hospital stay, stroke and renal injury. CONCLUSIONS: Patients who are re-explored for bleeding within 24 h have almost four-fold higher odds of mortality within 3 months post-procedure. However, the increased risk of death following re-exploration is not maintained in the long term. Abstract : Perioperative bleeding is a severe complication of cardiac surgical procedures, with reported re-exploration rates ranging between 2% and 7% in different studies [1–5].